Water quality characteristics in relation to mangrove disturbance levels - Nik Zaidin, Nik Harun Al-Rashid; Abu Bakar, Siti Nurhidayu; Mohamad Kasim, Mohamad Roslan (2016)
Mangroves are an important ecosystem that provides environmental protection and play a significant role in economic activity especially for fisheries and charcoal products. The mangrove ecosystem offers carbon absorption and shoreline protection against natural events. However, land conversion and poor land use management resulted in excessive pollution that might affect mangrove health, particularly hydrology. Variation in hydrological characteristics might be influenced by climate change which also affects the extreme events and climate cycles. Matang Mangrove Forest Reserve (MMFR) is a large contiguous mangrove forest in Peninsular Malaysia (40,466ha) known for its excellent management of timber. Aerial images were used to classify the different mangrove disturbance levels (e.g. least disturbed, moderately disturbed and mostly disturbed) and relates the conditions with water quality. Water quality data from 2004 to 2013 were acquired from the Department of Environment (DOE). The temporal variation of water quality characteristics was analysed in relation to the classification of mangrove disturbance levels. The finding indicates that three mangrove areas have different water quality conditions corresponding to its disturbance levels. This will be used to facilitate meteorological, hydrological and ecological assessment in mangroves for better management of mangroves in the future.